Examining the mediating role of resources in the temporal relationship between proactive burnout prevention and burnout - Madelon C. B. Otto; Joris Van Ruysseveldt; Nicole Hoefsmit; Karen Van Dam (BMC, 2021)
Abstract Background Employees who engage in proactive burnout prevention can prevent burnout by changing aspects of the work, home, and personal domain. However, these proactive behaviors may be impeded by high initial levels of burnout. Based on the conservation of resources theory and the dual-pathway proactivity model, resources were expected to play a vital role in the relationship between proactive burnout prevention and burnout through two distinct processes: a resource-generation process in which proactive burnout prevention negatively affects burnout through an increase in resources, and a resource-depletion process in which proactive burnout prevention is hindered because high initial levels of burnout negatively affected resources. Methods A two-wave longitudinal panel design was used in which 617 employees, mainly employed in government agencies, healthcare and education, were asked to complete an online survey twice with an interval of 1 month. Results Results of structural equation modelling showed clear evidence for the resource-generation process in the work, home, and personal domain, and only limited evidence for the resource-depletion process. Solely in the personal domain a small negative indirect effect of burnout on proactive burnout prevention through personal resources was found. Conclusions The findings of this study confirm that employees can proactively prevent burnout by investing in resources, yet proactive actions should be taken before increased burnout-complaints impede employees to do so. This study contributes to scientific knowledge on proactive behaviors and burnout prevention by investigating the mechanism underlying the temporal relationship between proactive burnout prevention and burnout. An important practical implication of this study is that it highlights that more attention should be given to employees' self-initiated actions to prevent burnout, as proactive burnout prevention can effectively reduce levels of burnout.